Exploring Pulung Gantung Tali Pati a study of memory and trauma on suicide by self-hanging / Ahmad Zamzuri - Zamzuri, Ahmad (2021)
Pulung Gantung Tali Pati is a Javanese novel written by Iman Budhi Santosa, an Indonesian poet, and writer. The novel narrates a character who traces the myth of death by body hanging in Gunung kidul, a regency in the Yogyakarta Special Region, Indonesia. This research aims to uncover death caused by hanging oneself through a memory and trauma study approach. Through this research, the research also tries to find out the causes and consequences of death caused by hanging suicide in public memory. As a result, this paper discovers; firstly, pulung gantung becomes part of memory and belief about suicide by entangling the neck with a rope and hanging himself in a higher position. Secondly, pulung gantung brings disaster to people and the area where the body falls. Thirdly, suicide creates traumatic memories, as well as a disgrace to the family and community in which it occurred. Fourthly, the narratives that reveal a different side of the suicide causes give the possibility that this novel tries to immerse new memories in readers in an attempt to break the chain of myths about suicide